Modeling of Annular Prediffuser for Marine Gas Turbine Combustor using CFD - A Study on the Effect of Strut Configuration (Journal of Naval Architecture and Marine Engineering, 2009)
This paper presents the numerical and experimental investigation of a straight core annular diffuser normally used in marine gas turbine combustor. The flow in the annular diffuser has been simulated by solving the equations for conservation of mass and momentum. For turbulence modeling the standard k-Îµ model is employed and the predicted results have been validated with experiments. A five-hole probe and a single normal hot wire anemometer were used to measure mean and fluctuating components of velocity. The comparison of the experimental and predicted mean velocity values in radial direction, at different axial locations of annular diffuser is presented and discussed. Flow development in the annular diffuser with different strut geometries has been analyzed. The discussion is focused on the distortion of the flow produced by the strut configuration. Keywords: Annular Diffuser, Struts, Recirculation Region Â  doi:10.3329/jname.v2i2.1871 Â Journal of Naval Architecture and Marine Engineering 2(2005) 41-52